A review of methods used for hazard identification and risk assessment of environmental hazards. (February 2019) - Chartres, Nicholas; Bero, Lisa A.; Norris, Susan L.
Abstract: Background: Approximately one quarter of all deaths globally are attributed to living or working in an unhealthy environment, with household and ambient air pollution, along with exposures to ultraviolet radiation and chemicals amongst the leading causes. At present there are no international standards for assessing the risks of these environmental hazards. The use of heterogeneous methods to identify health risks from environmental hazards may reduce the level of confidence the public has in the conclusions that are made. Objectives: To describe and compare the processes and methods used by national and international organisations that conduct hazard identification and/or risk assessment (HI/RA) of environmental hazards and to identify knowledge gaps to inform the development of future methods. Methods: We searched the websites of 19 organisations (ten national, five international and four World Health Organization (WHO) units) and extracted data from all relevant, publicly available resources which described the processes and methods used in HI/RA of environmental hazards. We contacted each organisation for any additional information. Results: Five organisations were excluded from further analysis: three made recommendations but did not conduct HI/RA; one used heterogenous methods across their reviews for HI; and one WHO unit did not have any published guidelines. Of the 14 organisations analysed, five (36%) describe the process for establishing the questions to be answered in the assessments. Only one (7%) organisation uses systematic review methods, although five (36%) state that they use such methods. Ten (71%) assess the scientific quality of the included studies, however only three (21%) use explicit criteria. Only three (21%) organisations assess the quality of the body of evidence using explicit criteria. Four (29%) organisations describe the process for making the final HI conclusions and three (38%) the final RA conclusions. Eight (57%) have a conflict of interest policy and seven (50%) organisations describe a process for managing them. The US Office of Health Assessment and Translation and the World Health Organisation meet the most criteria for describing their processes and methods. Conclusions: The processes and methods used by organisations conducting HI/RA of environmental hazards are inconsistent. There is a need for empirically based tools and methods to be adopted for the evaluation and synthesis of evidence, and the formulation of conclusions across all organisations that conduct HI or RA. These tools and methods will lead to increased transparency, comparability and validity of the assessments. Highlights: We describe the methods that 14 organisations use for HI/RA of environmental hazards. The reported methods are heterogeneous and frequently suboptimal. Only 1 organisation uses systematic review methods. Only 3 organisations assess study quality and 3 the quality of the body of evidence using explicit criteria. OHAT and a WHO unit best describe their methods.